Relationship Between Workload And Work Attitude On Employee Performance Is Mediated By Organizational Commitment - Susanto, Yohanes; Herlina, Herlina (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Purpose: This study examines how organizational commitment mediates the relationship between work attitude and workload and their combined impact on employee performance at the Secretariat of the Legislative Council in Musirawas District, South Sumatra, Indonesia. Methodology: A quantitative, correlational design was employed, with SEM-PLS analysis on data from 130 respondents selected via purposive sampling. Results: Work attitude significantly affects employee performance, with optimal work supported by promotions. Workload, when directed with efficient time use, positively impacts performance. Both work attitude and workload together significantly influence employee performance. Organizational commitment mediates these relationships. Findings: Organizational commitment, through promotions and leader appreciation, amplifies the impact of work attitude and workload on performance. Originality: The study highlights how optimal work attitudes supported by organizational commitment enhance employee capabilities, providing an innovative perspective on performance improvement. Novelty: It focuses on the unexplored link between work attitudes and organizational commitment. Conclusion: Organizational commitment acts as a critical mediator, suggesting that performance can be optimized by fostering a culture of appreciation and timely workload management. Type of Paper: Empirical research.